PROSES BERPIKIR ALJABAR SISWA MTs KELAS VIII MENURUT TAKSONOMI SOLO DITINJAU DARI PERBEDAAN GENDER - Lilia Sinta Wahyuniar; Niska Shofia; Siti Rochana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to describe the algebraic thinking process of grade VIII MTs students in solving algebraic problems based on Taksonomi Solo seen from gender differences in students with high mathematical abilities. The research was carried out in the eighth grade of Miftahul Huda MTs in Kediri Regency. The research subjects consisted of two students, namely women and men with high abilities. Subjects were chosen based on information from the teacher regarding mathematical abilities and the willingness and openness of the subject to be interviewed about the task of algebra problems. The results of the study showed that female students with high abilities fulfilled the indicators of algebraic thinking, namely finding certain tribes and generalizing the given patterns and understanding the role of variables as numbers that are known in algebraic form, equations and inequalities. Whereas male students with high abilities only fulfill the indicators of algebraic thinking, namely finding certain tribes in the given pattern.